Mowa niezależna w przekazie medialnym a podstawowe funkcje informacji dziennikarskiej (część 1) - Grzelka, Monika; Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The article is a part of outcome from a research project carried out by the author and devoted to quotations in Polish media and mass communication after 1989. The present elaboration includes an analysis of journalistic information, viewed as a particular kind of journalistic communication distinguishable from column writing due to its specific functions. A number of monographs and text books devoted to the development of the writing skills required for producing media texts are examined to single out those properties of journalistic information that the authors consider to be the most important. Within the context of the indications obtained in the process and the factographic pact between the author and the reader as it has been described by Zbigniew Bauer, the functions of quotation in direct speech are discussed. An attempt has been made to introduce a classification of persons using journalistic text in their presentations, while one of the their categories, a participant of described events, is examined more thoroughly.